2020
DOI: 10.1039/d0cc06817a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic chiral cyclohexanohemicucurbit[12]uril

Abstract: NMR spectroscopy and DFT modeling studies of chiral cyclohexanohemicucurbit[12]uril indicate that the macrocycle adopts a concave octagonal shape with two distinct conformational flexibilities in solution. Methylene bridge flipping occurs at...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This inspired us to explore further complexation and chirogenesis with bis-ZnOEP due to its aforementioned binding and chirality Recently, we reported that carbonyl groups of (R,R)-and (S,S)-enantiomers of barrelshaped macrocycles, cyclohexanohemicucurbit[n]urils (cycHC[n], n = 6, 8) (Figure 1), can externally bind multiple zinc porphyrins through the Lewis acid-base interactions and subsequently induce chirality at the porphyrin core [36]. A family of cycHC[n]s consists of chiral and nonchiral (n = 6, 8, 12) members [37][38][39][40] and features, analogous to all single bridged cucurbiturils [41,42], binding anions inside the macrocycle cavity. Additionally, cycHC[n]s bind hydrogen bond donors and electron-rich organic molecules [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…This inspired us to explore further complexation and chirogenesis with bis-ZnOEP due to its aforementioned binding and chirality Recently, we reported that carbonyl groups of (R,R)-and (S,S)-enantiomers of barrelshaped macrocycles, cyclohexanohemicucurbit[n]urils (cycHC[n], n = 6, 8) (Figure 1), can externally bind multiple zinc porphyrins through the Lewis acid-base interactions and subsequently induce chirality at the porphyrin core [36]. A family of cycHC[n]s consists of chiral and nonchiral (n = 6, 8, 12) members [37][38][39][40] and features, analogous to all single bridged cucurbiturils [41,42], binding anions inside the macrocycle cavity. Additionally, cycHC[n]s bind hydrogen bond donors and electron-rich organic molecules [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In Aav’s group, the first enantiomerically pure, inherently chiral member of the family—specifically cyclohexanohemicucurbit[6]uril (cycHC[6]) ( Aav et al, 2013 )—was prepared. Later, its larger homologs, cycHC[8] ( Prigorchenko et al, 2015 ) and cycHC[12] ( Mishra et al, 2020 ), were also made.…”
Section: Introductionmentioning
confidence: 99%
“…The latter grants these macrocycles the ability to encapsulate anions ( Buschmann et al, 2005 ; Cucolea et al, 2016 ; Kaabel et al, 2017 ; Assaf and Nau, 2018 ; Reany et al, 2018 ; Vázquez and Sindelar, 2018 ; Andersen et al, 2019 ; Kandrnálová et al, 2019 ; Valkenier et al, 2019 ; Maršálek and Šindelář, 2020 ); in addition, the formation of complexes with acids and some neutral species has been reported in the previous work. In particular, unsubstituted hemicucurbit[ n ]urils ( n = 6, 12) bind phenol derivatives ( Jin et al, 2016a ; 2016b ) and ferrocene ( Jin et al, 2017 ), and cyclohexanohemicucurbit[ n ]urils cycHC [ n ] ( n = 6, 8, 12) ( Li et al, 2009 ; Aav et al, 2013 ; Prigorchenko et al, 2015 , 2019 ; Mishra et al, 2020 ) form external complexes with both inorganic and organic acids ( Öeren et al, 2014 ; Ustrnul et al, 2019 , 2021 ). We envisioned that heterocycles 1–13 have relatively high electron densities compared to carbocycles and may therefore be able to occupy space within the eight-membered cycHC[8] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%